Transcriptome Analysis of Otodectes cynotis in Different Developmental Stages - He, Ran; Zhang, Qian; Gu, Xiaobin; Xie, Yue; Xu, Jing; Peng, Xuerong; Yang, Guangyou (Frontiers in Microbiology, 2022)
The mite Otodectes cynotis is distributed worldwide and parasitism the ear canals of cats and dogs, causing otitis externa. Molecular biology of O. cynotis is poorly understood, with only a few genes being deposited in public databases. In the present study, we aimed to perform transcriptome analysis of O. cynotis using SMRT and Illumina sequencing of RNA from different development stages. SMRT-Seq of O. cynotis demonstrated 5,431 final transcripts, including 406 long noncoding RNAs and 2,698 differentially expressed genes, including 1,357 up-regulated genes and 1,341 down-regulated genes between adult mites and nymph/larva. A total of 397 putative allergen genes were detected, 231 of which were differentially expressed genes. Among them, 77 were homologous of known mite allergens. The expression level of allergen genes hints at the pathogenicity of mites in different life stages, and the protein interaction network analysis could identify possible key genes in the pathogenic mechanism. Intriguingly, Gene Ontology analysis showed that most of the differentially expressed genes were associated with the terms hydrolase activity and proteolysis. Kyoto Encyclopedia of genes and genomes analysis identified drug metabolism-cytochrome P450 signal pathway as one of the top pathways. SMRT-Seq of the full-length transcriptome of O. cynotis was performed first, and a valuable resource was acquired through the combination analysis with the Illumina sequencing data. The results of our analyses provide new information for further research into Otodectes cynotis.